Executive compensation and executive incentive problems - Lewellen, Wilbur; Loderer, Claudio; Martin, Kenneth (Journal of Accounting and Economics, 1987)
The question of whether the design of the corporate executive pay package reflects an attempt to reduce agency costs between shareholders and managers is addressed. The components of senior executive pay are found to vary systematically across firms in a manner that cannot easily be explained by tax effects, and which would indicate that individual elements of pay are aimed at controlling for limited horizon and risk exposure problems. Managerial decisions and the structure of managerial pay therefore appear to be interrelated.